When Should Developing Countries Announce Their Climate Policy? - Jorge Fernandez; Sebastian Miller (Inter-American Development Bank (IDB), 2011)
This paper provides a rationale for developing countries to announce future credible commitments to reduce GHG emissions even if these are not to materialize in the short run, and for domestic reasons only. A simple framework is presented in which it is shown that it may be costly for an economy to transition from high to low emissions; and that, if climate policy eventually will be enacted, then it may be better for countries to commit earlier and therefore eliminate the uncertainty for the private sector to invest appropriately in clean technologies. In particular, conditions are shown under which the private investor prefers a pre-announced climate policy, and how this policy affects investment decisions and the deployment of clean technologies.
Keywords: D81; H23; Q54; 330